Postoperative adjuvant chemotherapy in patients with stage II early onset colorectal cancer: exploration and discovery using real-world data and the SEER database - Cao, Shikun; Qiao, Yihuan; Wu, Lijun; Chen, Qi; Tian, Kai; Li, Jipeng; Xing, Chungen (Frontiers in Oncology, 2025)
Background and aimThe incidence of early-onset colorectal cancer (EOCRC) is rising, yet intensive postoperative adjuvant chemotherapy (ACT) often results in overtreatment with minimal prognostic benefit. This study aims to assess the therapeutic necessity of ACT in stage II EOCRC patients and to identify potential ACT candidates.MethodsA total of 296 non-ACT and 50 ACT patients with stage II EOCRC were included from Xijing Hospital (XJCRC), and 2067 non-ACT and 1163 ACT patients were enrolled from the Surveillance, Epidemiology, and End Results (SEER) cohort. To address selection bias and confounding, propensity score matching, inverse probability treatment weighting (IPTW), and multivariate Cox regression analyses were utilized. Survival curves and landmark analysis were employed to compare Overall Survival (OS) differences.ResultsSimilar OS were observed between ACT and non-ACT groups in both cohorts before and after adjustment for confounders. No significant survival differences were noted in dMMR (P = 0.48), pMMR (P = 0.07), and T3 (P = 0.83) subgroups. However, T4 stage patients receiving ACT demonstrated prolonged survival compared to non-ACT counterparts, particularly after three years (P = 0.007), as identified by landmark analysis.ConclusionsMost stage II EOCRC patients might yield limited benefits from postoperative ACT, with the sole exception of those at T4 stage, who could experience long-term clinical advantages.Clinical Trial Registrationhttps://clinicaltrials.gov/study/, identifier NCT06308354.